Effect of High-Pressure Processing Treatment on the Physicochemical Properties and Volatile Flavor of Mercenaria mercenaria Meat - Xingli Xue; Di Wang; Min Li; Yongren Li; Yongjun Guo; Xiaoqing Ren; Chunsheng Li (Molecules)
High-pressure processing (HPP) technology can significantly improve the texture and flavor of Mercenaria mercenaria. This study aimed to investigate the effect of HPP treatment with varying levels of pressure (100, 200, 300, 400, 500, and 600 MPa) and a holding time of 8 min at 20 °C on the physicochemical properties and volatile flavors of M. mercenaria. The significant changes in hardness, resilience, and water holding capacity occurred with increasing pressure (p < 0.05), resulting in improved meat quality. Scanning electron microscopy (SEM) was utilized to observe the decomposition of muscle fibers in M. mercenaria due to varying pressures, which explains the differences in texture of M. mercenaria. Different pressure treatments also had an influence on the volatile flavor of M. mercenaria, and the quantities of low-molecular-weight aldehydes (hexanal, heptanal, and nonanal) with a fishy taste decreased dramatically following 400 and 500 MPa HPP treatments. Furthermore, the level of 2-Methylbutyraldehyde, which is related to sweetness, increased significantly following 400 MPa HPP treatment. The study found that 400 MPa HPP treatment resulted in minor nutrient losses and enhanced sensory quality. The results of this study provide a theoretical basis for the application of HPP treatment to M. mercenaria.